Bucking and charging defense of Baird’s tapir (Tapirella bairdii) from common vampire bats (Desmodus rotundus) - Amit, Ronit; Valverde-Zúñiga, Natalia (Therya Notes, 2022)
Camera trap studies have captured a wide diversity of wildlife behaviors, highlighting the importance of behavioral ecology in meeting wildlife management and conservation goals. We report on predation attempts by common vampire bats (Desmodus rotundus) upon Baird's tapir (Tapirella bairdii) and describe the tapir's defensive response. On September 2020, we obtained the records of this interspecific interaction at one camera-trap station located in a buffer zone of the Rincon Rainforest Reserve in northwestern Costa Rica. We recorded vampire attempts to feed on at least 2 individuals of Baird’s tapirs. When detecting the bats, tapirs reacted to repel them by shacking, running, spinning, and chasing the bats in flight. These cases add to our current knowledge of tapirs’ defensive behavior and are relevant to questioning the evolution of stealthiness in vampire attacks. In addition, it emphasizes the role of monitoring these interspecific interactions in relation to zoonosis in human-modified landscapes.